Identification of a caleosin associated with hazelnut (Corylus avellana L.) oil bodies. (10th March 2020) - Lamberti, C.; Nebbia, S.; Balestrini, R.; Marengo, E.; Manfredi, M.; Pavese, V.; Cirrincione, S.; Giuffrida, M. G.; Cavallarin, L.; Acquadro, A.; Abbà, S.
Abstract: Caleosins are involved in several cellular and biological processes that are closely associated with the synthesis, degradation and stability of oil bodies (OB). Because of the importance and the multiple roles of these OB‐associated proteins, in silico identification of sequences corresponding to putative caleosins in the hazelnut genome has been performed, and the association with seed OB was verified using a proteomic approach. Five full‐length sequences (CavCLO‐H1, CavCLO‐H2, CavCLO‐H3, CavCLO‐L1, CavCLO‐L2), belonging to the two groups of caleosins (H and L), have been identified in the hazelnut genome. The number of identified caleosins is in agreement with that previously observed in other plant species, confirming that caleosins comprise small gene families in plants. A proteomic approach allowed us to verify only the presence of CavCLO‐H1 in hazelnut OB, suggesting that several members inside this family could have different roles during plant growth and development. In silico analysis also suggests that CavCLO‐H1 may act as a peroxygenase. Abstract : Several caleosin sequences were identified in the hazelnut genome and one of them (CavCLO‐H1) was found to be associated to seed oil bodies.